Penerapan Teknologi Informasi Berbasis Web Di Badan Amil Zakat Nasional (BAZNAS) - Khasanah, Nevi Laila; Manora, Hecksa (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
The National Amil Zakat Agency (BAZNAS) is one approach to overseeing zakat as far as collecting, distributing and utilizing zakat. The presence of Baznas must continue to be worked out through the methodology of institutional reform so that governance and use can run productively, successfully and relatively so that it can affect the work of regional finances. One of the methodologies used to undermine the organization of zakat foundations is to expand the use of electronic information systems as a medium to cooperate and work on the efficiency of zakat leaders in the sorting, transportation and utilization of zakat. The results show that 34% of new BAZNAS in Indonesia have involved the SIMBA application as an application used to lead the details of monetary organizations, while for Communities and Supporters of several BAZNAS.